Meningkatkan Kualitas Pelayanan Jalan Raya Plandaan – Boro Tulungagung Menggunakan Perkerasan Kombinasi Geotextile - Muhammad Ridho; Yosef Cahyo Setianto Poernomo; Agata Iwan Candra; Fajar Romadhon (Faculty of Engineering, Kadiri University, 2021)
Roads as a means of transportation have an essential role in supporting human activities. One of the developments in road construction is the application of geotextiles in road combination pavements. Geotextile itself is often found in construction planning, especially in soil stabilization. The plandaan – boro Tulungagung road section is indicated by the type of silt as deep as 1.2 meters so that improvements are needed to support the quality of road construction. The purpose of this research is to plan road pavement with geotextiles on the Plandaan to boro roads. The geotextile used is a woven geogrid geotextile. The method used in planning is the Bina marga method of the 2017 Road Pavement Design Manual. The data used include technical data, traffic data, and California Bearing Ratio (CBR). The planning includes traffic design, pavement thickness calculations, and volume calculations. The planning results will be HMA – WC pavement covering an area of 4,200 m, with K225 concrete pavement covering an area of 8,400 m. Class Bﬞ Aggregate Pavement covering an area of 10,500 m using a geotextile layer requires 51,000 m² so that these results can be used as a reference in the repair or improvement of the Plandaan - boro Tulungagung road.